Contributions of Hot and Cool Self-Regulation to Preschool Disruptive Behavior and Academic Achievement - Willoughby, Michael (Dev Neuropsychol, 2011)
The construct of self-regulation can be meaningfully distinguished into hot and cool components. The current study investigated self-regulation in a sample of 926 children aged 3–5 years old. Children’s performance on self-regulatory tasks was best described by two latent factors representing hot and cool regulation. When considered alone, hot and cool regulation were both significantly correlated with disruptive behavior and academic achievement. When considered together, cool regulation was uniquely associated with academic achievement, while hot regulation was uniquely associated with inattentive-overactive behaviors. Results are discussed with respect to treatment studies that directly target improvement in children’s self-regulation.